Value Engagement of TikTok: A Review of TikTok as Learning Media for Language Learners in Pronunciation Skill - Tira Nur Fitria (The Study Program of English Education of Palangka Raya University, 2023)
This study describes the use of TikTok as a medium for Language Learners in learning pronunciation. This study uses a descriptive qualitative. The research uses Exolyt as an analytical tool to determine engagement values including clicks, comments, and shares. The researcher uses five popular content creators, namely @englishwithgeet, @english.with.luccy, @englishwithcarla, @englishwithnab, and @andreaholmenglish. The analysis shows that the pronunciation category has the highest engagement because pronunciation is one of the important elements in English speaking and short video duration is very suitable for this category. It shows clear sound, images, filters, and material in the delivery of material, attractive images (right light), and the influence of the creator and material presented is more specific and clear. These videos from @english.with.lucyy and @englishwithnab consist of phonetic symbols. The use of the phonetic symbol is important in learning pronunciation to make it easier for viewers or English learners in pronouncing English words correctly. Besides pronunciation, the learners also can learn grammar, vocabulary, and common mistakes in English. TikTok application, together with the proper use and method can be used as an interesting, interactive, and innovative learning medium in learning even teaching English.